Empowering Women in Rural Tourism Development at Saung Ciburial Tourism Village, Garut, Indonesia - Rachmat Syam (Syntax Literate, 2022)
In this modern era, every human being has the same right to work including in the development of tourism in a destination. Likewise, women deserve an equal share and are empowered. Rural tourism is not only alternative tourism but is a vital aspect of the community’s socio-economic development. Rural tourism is also an important tool in upholding the principle of gender equality because women take a large role in employment relations in rural tourism development. The main focus of this research is to review the extent of women's empowerment in the development of rural tourism in the Saung Ciburial Tourism Village, Garut City. Using descriptive methods and qualitative approaches, data collection was carried out through observation and integrated interviews where the participants in this study were all stakeholders and women who were involved in rural tourism activities in Saung Ciburial Tourism Village. The results showed that women in the Saung Ciburial Tourism Village had been actively involved/empowered in tourism activities, starting from technical staff, lower-level management, to upper-level management where they were trusted to be administrators and even leaders of village government organizations/agencies.